Rational design of coumarin derivatives as antituberculosis agents - Mali, Hemlata M.; Sabale, Sandip S.; Degani, Mariam S.; Borkute, Rachana; Choudhari, Amit S.; Sarkar, Dhiman; Krishna, Vagolu Siva; Sriram, Dharmarajan (Future Medicinal Chemistry, 2018)
A series of coumarin derivatives was designed as potential antituberculosis agents. Results: The compounds were screened against active and dormant Mycobacterium tuberculosis (Mtb). Compounds 3k and 3n were found to have the most promising activity against replicating MtbH37Rv exhibiting minimum inhibitory concentration of 4.63 and 9.75 mu M respectively. The compounds were also effective against dormant MtbH37Rv exhibiting more potency than the standard drugs, isoniazid and rifampicin. The compounds were found to be non-cytotoxic against human cell lines. Conclusion: This study provides promising antituberculosis agents that are effective against replicating as well as dormant Mtb and can thus act as potential leads for further development.

Synthesis and biological evaluation of 2,4,5-trisubstituted thiazoles as antituberculosis agents effective against drug-resistant tuberculosis - Karale, Uttam B.; Krishna, Vagolu Siva; Krishna, E. Vamshi; Choudhari, Amit S.; Shukla, Manjulika; Gaikwad, Vikas R.; Mahizhaveni, B.; Chopra, Sidharth; Misra, Sunil; Sarkar, Dhiman; Sriram, Dharmarajan; Dusthackeer, V. N. Azger; et al. (European Journal of Medicinal Chemistry, 2019)
The dormant and resistant form of Mycobacterium tuberculosis presents a challenge in developing new anti-tubercular drugs. Herein, we report the synthesis and evaluation of trisubstituted thiazoles as antituberculosis agents. The SAR study has identified a requirement of hydrophobic substituent at C2, ester functionality at C4, and various groups with hydrogen bond acceptor character at C5 of thiazole scaffold. This has led to the identification of 13h and 13p as lead compounds. These compounds inhibited the dormant Mycobacterium tuberculosis H37Ra strain and M. tuberculosis H37Rv selectively. Importantly, 13h and 13p were non-toxic to CHO cells. The 13p showed activity against multidrug-resistant tuberculosis isolates. (C) 2019 Elsevier Masson SAS. All rights reserved.

Design and synthesis of novel quinazolinyl-bisspirooxindoles as potent anti-tubercular agents: an ultrasound-promoted methodology - Allaka, Bhargava Sai; Basavoju, Srinivas; Rekha, Estharla Madhu; Sriram, Dharmarajan; Krishna, Gamidi Rama (Molecular Diversity, 2023)
The essential need for the potent anti-tubercular (anti-TB) agents with high selectivity and safety profile prompted us to synthesize a new series of quinazolinyl-bisspirooxindoles. The title compounds were synthesized by one-pot multicomponent [3 +2] cycloaddition reaction under ultrasonication. Further, in vitro anti-TB activity was evaluated against Mycobacterium tuberculosis H37Rv. Among the screened compounds, two compounds (4q and 4x) showed potent activity with MIC value 1.56 mu g/mL and four compounds exhibited significant activity (MIC =3.125 mu g/mL), and also cytotoxicity studies against RAW 264.7 cell lines reveal that most active compounds were less toxic to humans. In addition, in order to demonstrate the inhibitory properties, molecular docking studies were carried out and the results showed that the target compounds have good binding energy and better binding affinity within the active pocket, thus these compounds may consider to be as potent inhibitors toward selective targets.
Keywords: anti-tubercular activity; bisspirooxindoles; Cytotoxicity screening; Molecular docking studies; ultrasonication

Design, synthesis, anti-mycobacterial activity, molecular docking and ADME analysis of spiroquinoxaline-1,2,4-oxadiazoles via [3+2] cycloaddition reaction under ultrasound irradiation - Kanchrana, Madhu; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (MOLECULAR DIVERSITY, 2024)
Keywords: 2; 4-oxadiazoles; cytotoxicity activity; molecular; Mycobacterium tuberculosis; Spiroquinoxaline-1

Ultrasound-assisted ionic liquid-mediated green method for synthesis of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidines, their anti-tubercular activity, molecular docking study and ADME predictions - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (New Journal of Chemistry, 2024)
The aim of the study is to develop the synthesis of a novel series of potent anti-tubercular (anti-TB) activity of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives via an efficient green approach achieved by using an ionic liquid ([Bmim]BF4) under ultrasonication. The title compounds 4a-4ad with a general molecular formula CaHbX(0-2)NcOd (X = F/Cl/Br) were produced with high yields in shorter reaction time and well characterized by using spectral techniques; and finally single crystal X-ray diffraction method (4b). The newly synthesized compounds were evaluated for their in vitro anti-TB activity against Mycobacterium tuberculosis H37Rv strain. Among all, six compounds 4e (C36H29N5O4), 4g (C34H28N4O3), 4q (C36H28F2N4O2), 4r (C36H28ClFN4O2), 4y (C36H29BrN4O2) and 4z (C36H28BrFN4O2) exhibited significant anti-TB activity with MIC value 6.25 mu g mL-1, when compared to the standard drug ethambutol (MIC:1.56 mu g mL-1). In silico molecular docking studies were performed against M. tuberculosis enoyl-acyl carrier protein reductase inhibitor. The compounds 4o, 4p, 4y and 4aa were exhibited least binding energies -12.58, -12.61, -12.58 and -12.57 kcal mol-1, respectively. These results reveal that the produced compounds might be used for the future generation of novel anti-TB drugs. The study aims to develop and synthesis of a novel series of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives as potent anti-TB agents via an efficient green approach by using an ionic liquid ([Bmim]BF4) under ultrasonication.

Green one-pot three component synthesis of thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidines with [Bmim]BF4: their in vitro and in silico anti-TB studies - Rukyanaik, V.; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (Molecular Diversity, 2025)
A simple and effective three-component one-pot green methodology was employed for the synthesis of a new thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidine derivatives using [Bmim]BF4 ionic liquid via [3 + 2] cycloaddition reaction. It is an environmentally benign, column chromatography-free, shorter reaction time, good yield and easy product isolation method. The synthesized compounds 10a-x, were thoroughly characterized by using various spectroscopic methods like FT-IR, H-1 NMR, C-13 NMR, Mass spectrometry and finally by single crystal X-ray diffraction method. In vitro anti-tubercular (anti-TB) activity studies were carried out on these synthesized compounds, and they showed good to moderate anti-TB activity against Mycobacterium tuberculosis H37Rv strain. The compound 10a exhibited good anti-TB activity, with an MIC (Minimum Inhibitory Concentration) value of 12.5 mu g/mL, and the compounds 10m, 10o and 10r showed moderate activity with an MIC value of 25.0 mu g/mL. Remaining compounds exhibited poor activity against Mycobacterium tuberculosis. Ethambutol, rifampicin and isoniazid were used as standard drugs. Furthermore, in silico molecular docking experiments on the TB protein (PDB ID: 1DF7) were carried out to understand the binding interactions, and they showed least binding energy values ranging from -8.9 to -7.2 kcal/mol.
Keywords: 4-dione based bisspirooxindolo-pyrrolidines; Anti-TB activity; green synthesis; Molecular docking; Thiazolidine-2; [3+2] cycloaddition reaction; [Bmim]BF4

An ultrasound-assisted green synthesis of 1,3-diphenyl pyrazole-based spirooxindolo-1,2,4-oxadiazoles: their in vitro anti-tubercular activity and in silico molecular dynamics - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Gangarapu, Kiran; Basavoju, Srinivas (Chemistryselect, 2025)
A simple base-mediated one-pot synthetic green methodology has been successfully employed for the synthesis of 1,3-diphenylpyrazole-based spirooxindolo-1,2,4-oxadiazole derivatives. The newly synthesized analogues were tested for their in vitro anti-tubercular activity (anti-TB) against Mycobacterium tuberculosis H37Rv strain, and the results were reported as minimum inhibitory concentration (MIC) values ranging from 3.125 to 25 mu g/mL. Especially, the five compounds 3a, 3f, 3k, 3q, and 3v exhibited good to moderate anti-TB activity with MIC of 3.125 mu g/mL when compared to the reference drug ethambutol (MIC: 1.56 mu g/mL). In silico Molecular docking and molecular dynamics simulations of the protein-ligand complex (3a, 3f, 3k, and 3v) against Mycobacterium tuberculosis DprE1 (PDB ID: 5OEQ) of M. tuberculosis H37Rv strain revealed that these four compounds could be promising anti-mycobacterial candidates, as evident from the binding results and stability of the docked-ligand complexes with considerable least binding energies. ADME parameters were also studied to assess the drug likeness, which clearly shows that the newly developed compounds might be useful for the future development of novel anti-tubercular drugs.
Keywords: 1; 2; 4-oxadiazoles; In silico molecular dynamic studies; In vitro anti-tubercular activity; ultrasonication